2016
DOI: 10.1071/ah15073
|View full text |Cite
|
Sign up to set email alerts
|

Reducing hospitalisation among people living with severe mental illness

Abstract: Objective People with severe mental illness have high rates of hospitalisation. The present study examined the role that permanent housing and recovery-oriented support can play in reducing the number and length of psychiatric hospital admissions for people with severe mental illness. Methods The study examined de-identified, individual-level health records of 197 people involved in the New South Wales Mental Health Housing and Accommodation Support Initiative (HASI) to compare changes in hospitalisation over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 9 publications
3
17
0
Order By: Relevance
“…For this group of papers, service types ranged from intensive congregate residential care settings, with 24 h staffing [ 76 , 78 80 , 87 , 89 , 93 , 95 ], to less intensively supported accommodation, including group homes and supervised individual apartments (e.g. staffed 9 am-5 pm daily) [ 74 , 78 , 81 , 82 , 90 , 92 94 ], to individual tenancies with outreach support (staff based off-site) [ 75 , 81 , 83 , 87 , 88 , 90 , 96 ]. Other service descriptions lacked detail and were unable to be confidently categorised, including “sheltered housing” [ 77 ], “sheltered-care facilities” [ 86 ], “community-based housing” [ 91 ], “transitional, high-expectation, sheltered care environment” [ 85 ] and “support house” [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this group of papers, service types ranged from intensive congregate residential care settings, with 24 h staffing [ 76 , 78 80 , 87 , 89 , 93 , 95 ], to less intensively supported accommodation, including group homes and supervised individual apartments (e.g. staffed 9 am-5 pm daily) [ 74 , 78 , 81 , 82 , 90 , 92 94 ], to individual tenancies with outreach support (staff based off-site) [ 75 , 81 , 83 , 87 , 88 , 90 , 96 ]. Other service descriptions lacked detail and were unable to be confidently categorised, including “sheltered housing” [ 77 ], “sheltered-care facilities” [ 86 ], “community-based housing” [ 91 ], “transitional, high-expectation, sheltered care environment” [ 85 ] and “support house” [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve papers, including two high quality [ 92 , 94 ] and ten moderate quality studies [ 74 , 77 , 78 , 81 , 82 , 84 , 88 90 , 96 ], reported data relating to changes in rates of hospitalisation. The findings were mixed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-English language papers were excluded to ensure faithful application of the taxonomies. The final pool consisted of 132 service descriptions across 101 papers (quantitative: 95 service descriptions across 72 papers; qualitative: 37 service descriptions across 29 papers) [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,…”
Section: Resultsmentioning
confidence: 99%
“…This “housing first” initiative acknowledges and has demonstrated the importance of stable housing to mental health outcomes (Bullen & Fisher ; McDermott et al. ). It also speaks to the indistinctness of the line between housing support and other types of support, as general supports for mental health and social inclusion are also critical for maintenance of accommodation (O'Brien et al.…”
Section: Discussionmentioning
confidence: 99%